Analysis of the Implementation of the Contextual Science Teaching Factory Learning Model at the Medan City Center of Excellence Vocational School - Saut Purba; Marjuang Purba; Keysar Panjaitan; Abdul Hasan; Lisa Melvi Ginting (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to describe and determine the implementation of the Contextual Science Based Teaching Factory learning model at the Medan City Center of Excellence Vocational School and the factors inhibiting the implementation of the Contextual Science Based Teaching Factory learning model at the Medan City Center of Excellence Vocational School. This research is a qualitative descriptive study. The subjects in this research were 10 teachers who taught, 10 industrial partners and. and 25 class XI students at the Excellence Central Vocational School, Medan City. Data collection techniques were carried out using unstructured interviews and closed questionnaires. Before the research instrument is used, a validity test is first carried out using the Pearson Product Moment Correlation formula and a reliability test using the Cronbach's Alpha formula. The results of this research found that in the Context aspect it went well, in the Input aspect it went well and in the Process aspect it also went well but in the Product aspect it still went less well. Through this research it is hoped that the role of the stakeholders will be more optimal so that the Teaching Factory learning model is Contextually Based Science can proceed according to expectations.